Research status of soft anthropomorphic dexterous hands - LIU Yibo; XIAO Huaping; LIU Chuanwang; SUN Zhenhao; HAO Tianze; LIU Shuhai (Jixie chuandong)
SignificanceSoft anthropomorphic dexterous hands, as a type of robot end effector composed of soft materials, are capable of achieving human-like grasping and manipulation abilities, and are characterized by high dexterity, outstanding environmental adaptability, and safety in the human-robot interaction. [Analysis] The performance of soft anthropomorphic dexterous hands in terms of dexterity and grasping operation capabilities was reviewed, followed by a detailed introduction and analysis of the research status of soft anthropomorphic dexterous hands in terms of driving methods, materials and manufacturing, flexible tactile sensing, modeling and control. Finally, the potential challenges and possible development directions faced by soft anthropomorphic dexterous hands were discussed, and emphasizing that improving their dexterity and tactile perception capabilities is a key focus of future research.